Extraction of accurate cytoskeletal actin velocity distributions from noisy measurements - Cayla M. Miller; Elgin Korkmazhan; Alexander R. Dunn (Nature Communications, 2022)
Dynamic remodeling of the actin cytoskeleton underlies cell movement, but is challenging to characterize at the molecular level. Here, the authors present a method to extract actin filament velocities in living cells, and compare their results to current models of cytoskeletal dynamics.